Integration and analysis of the effects of an unnatural amino acid into transmembrane 4 of the Orai1 protein - Gemeinhardt, Helene Sabine (Jihočeská univerzita, 2023)
In this work intramolecular interactions of the Orai1 protein are investigated by integrating the unnatural amino acid p-Azido-L-phenylalanine (Azi) at different positions (A254, V252 and G247) of the Orai's transmembrane domain 4 (TM4). The compound Azi is unreactive under physiological conditions but can be activated using UV-light. Being reactive it can form covalent bonds with nearby residues. It is suspected that that residue A254 on TM4 is close enough to TM3 for the Azi to cross-link these two transmembrane domains. Positions V252 and G247 are assumed to be too far apart for crosslinking.
Integration and analysis of the effects of an unnatural amino acid into transmembrane 4 of the Orai1 protein
Keywords: Orai1; TM4; intramolecular protein interactions; unnatural amino acid; p-Azido-L-phenylalanine; Orai1; TM4; intramolecular protein interactions; unnatural amino acid; p-Azido-L-phenylalanine